Down-regulation of NTPDase2 and ADP-sensitive P2 Purinoceptors Correlate with Severity of Symptoms during Experimental Autoimmune Encephalomyelitis - Jakovljevic, Marija; Lavrnja, Irena; Bozic, Iva; Savic, Danijela; Bjelobaba, Ivana; Pekovic, Sanja; Sévigny, Jean; Nedeljkovic, Nadezda; Laketa, Danijela (Frontiers in Cellular Neuroscience, 2017)
The present study explores tissue and cellular distribution of ectonucleoside triphosphate diphosphohydrolase 2 (NTPDase2) and the gene and protein expression in rat spinal cord during the course of experimental autoimmune encephalomyelitis (EAE). Given that NTPDase2 hydrolyzes ATP with a transient accumulation of ADP, the expression of ADP-sensitive P2 purinoceptors was analyzed as well. The autoimmune disease was actively induced in Dark Agouti female rats and the changes were analyzed 10, 15, and 29 days after the induction. These selected time points correspond to the onset (Eo), peak (Ep) and recovery (Er) from EAE. In control animals, NTPDase2 was confined in the white matter, in most of the GFAP-immunoreactive (ir) astrocytes and in a considerable number of nestin-ir cells, while the other cell types were immunonegative. Immunoreactivity corresponding to NTPDase2 decreased significantly at Eo and Ep and then returned to the baseline levels at Er. The preservation of the proportion of GFAP single-labeled and GFAP/NTPDase2 double-labeled elements along the course of EAE indicated that changes in NTPDase2-ir occurred at fibrous astrocytes that typically express NTPDase2 in normal conditions. Significant downregulation of P2Y1 and P2Y12 receptor proteins at Eo and several-fold induction of P2Y12 and P2Y13 receptor proteins at Ep and/or Er were observed implying that the pathophysiological process in EAE may be linked to ADP signaling. Cell-surface expression of NTPDase2, NTPDase1/CD39 and eN/CD73 was analyzed in CD4+ T cells of a draining lymph node by fluorescence-activated cell sorting. Induction of EAE was associated with a transient decrease in a number of CD4+ NTPDase2+ T cells in a draining lymph node, whereas the recovery was characterized by an increase in NTPDase2+ cells in both CD4+ and CD4- cell populations. The opposite was found for NTPDase1/CD39+ and eN/CD73+ cells, which slightly increased in number with progression of the disease, particularly in CD4- cells, and then decreased in the recovery. Finally, CD4+ NTPDase2+ cells were never observed in the spinal cord parenchyma. Taken together, our results suggest that the process of neuroinflammation in EAE may be associated with altered ADP signaling.